2014
DOI: 10.1007/s10461-014-0710-6
|View full text |Cite
|
Sign up to set email alerts
|

HIV Prevalence and Risk Behaviors Among African American Women Who Trade Sex for Drugs Versus Economic Resources

Abstract: Trading sex for money, drugs, goods, services, or a place to stay is prevalent among women who use drugs and has been associated with women's risk of HIV acquisition. There is evidence that trading sex for drugs only may be associated with elevated risk of HIV compared with trading sex for money. The purpose of this study was to assess whether HIV risk behaviors and HIV prevalence differ among African American drug using women (N = 92) who traded sex for drugs only, traded sex for economic resources (defined a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…Although this study used an assessment with established psychometrics (Darke et al, 1991), women may underreport their involvement in high risk behaviors given the sensitive nature of the questions. In addition, women who trade sex for drugs may differ from women trading sex for money in their clinical characteristics and risk behaviors (Dunne et al, 2014; Kwiatkowski and Booth, 2000). For example, women who trade sex for drugs are less likely to use condoms and more likely to be HIV positive than women who trade sex for money (Dunne et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this study used an assessment with established psychometrics (Darke et al, 1991), women may underreport their involvement in high risk behaviors given the sensitive nature of the questions. In addition, women who trade sex for drugs may differ from women trading sex for money in their clinical characteristics and risk behaviors (Dunne et al, 2014; Kwiatkowski and Booth, 2000). For example, women who trade sex for drugs are less likely to use condoms and more likely to be HIV positive than women who trade sex for money (Dunne et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, women who trade sex for drugs may differ from women trading sex for money in their clinical characteristics and risk behaviors (Dunne et al, 2014; Kwiatkowski and Booth, 2000). For example, women who trade sex for drugs are less likely to use condoms and more likely to be HIV positive than women who trade sex for money (Dunne et al, 2014). This study assessed sex trading for drugs or money in a single question and is unable to examine whether women who trade sex for drugs differ in respect to their risk level, treatment response, or likelihood of continued involvement in sex trade from those who trade sex for money.…”
Section: Discussionmentioning
confidence: 99%
“…Women living in poverty, often with drug or alcohol problems are at high risk for sexually transmitted diseases including HIV, unwanted pregnancies, abortions, discrimination, criminalization and abuse when engaging in transactional sex [34]. Studies from an urban emergency room and family planning clinic found that 8% of women reported recently trading sex for money [35, 36]. Although trading sex for drugs or money is most often discussed in the context of sex workers, poverty and economic insecurity can motivate sexual decision making and risk taking in general.…”
Section: Discussionmentioning
confidence: 99%
“…The groundbreaking study by Kwiatkowski and Booth (Kwiatkowski & Booth, 2000) introduced the paradigm of separating these three groups from each other for analysis purposes. This was followed-up by Dunne et al to the extent that they could with their small sample size (Dunne et al, 2014). We have tried to follow in this tradition, and we had a large enough sample that enabled us to introduce additional re-finements into this approach to the study of drug using sex traders.…”
Section: Discussionmentioning
confidence: 99%
“…They also found that women who exchanged sex for money only were more likely to inject. A second study done in Baltimore found that those who only traded for drugs were more at risk for HIV because of lower condom use (Dunne et al, 2014). Because the sample size was small ( n = 92), they were only able to compare those who traded for both compared to those who traded for drugs only.…”
Section: Introductionmentioning
confidence: 99%